2019
DOI: 10.21203/rs.2.10894/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 2/1 sunitinib dosing schedule provides superior antitumor effectiveness and less toxicity than a 4/2 schedule for metastatic renal cell carcinoma: A systematic review and meta-analysis

Abstract: Background The standard sunitinib schedule to treat metastatic renal cell carcinoma (mRCC) is 4 weeks on/2 weeks off (4/2). However, some studies revealed intolerable adverse events (AEs) in patients on this schedule. An alternative schedule, 2 weeks on/1 week off (2/1), may overcome this issue. This meta-analysis was performed to compare the effectiveness and toxicity between the 2/1 and 4/2 sunitinib dosing schedules. Methods We acquired relevant studies by searching PubMed, ScienceDirect, the Cochrane Li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This indicates the need to manage the severe adverse effects, although the 2/1 schedule treatment had less sunitinibrelated severe toxicity among patients with metastatic renal cell carcinoma. 7,19 In this study, the median total sunitinib concentration in patients with severe adverse effects was significantly higher compared with that in patients without severe adverse effects. We observed a patient who exhibited a high total sunitinib concentration (sunitinib, 106 ng/mL; N-desethyl sunitinib, 27.9 ng/mL) on day 10 postinitiation and experienced grade 3 diarrhoea during the 2/1 schedule of sunitinib.…”
Section: 6mentioning
confidence: 50%
See 2 more Smart Citations
“…This indicates the need to manage the severe adverse effects, although the 2/1 schedule treatment had less sunitinibrelated severe toxicity among patients with metastatic renal cell carcinoma. 7,19 In this study, the median total sunitinib concentration in patients with severe adverse effects was significantly higher compared with that in patients without severe adverse effects. We observed a patient who exhibited a high total sunitinib concentration (sunitinib, 106 ng/mL; N-desethyl sunitinib, 27.9 ng/mL) on day 10 postinitiation and experienced grade 3 diarrhoea during the 2/1 schedule of sunitinib.…”
Section: 6mentioning
confidence: 50%
“…6 However, a recent meta-analysis demonstrated that the alternative dosing schedule, 2-week-on and 1-week-off schedule (2/1 schedule), is more effective [improved progression-free survival (PFS)] than the 4/2 schedule for the treatment of metastatic renal cell carcinoma. 7 Moreover, the 2/1 schedule is associated with less sunitinib-related severe toxicity and better tolerability among patients with metastatic renal cell carcinoma. 7,8 Sunitinib is primarily metabolized by cytochrome P450 (CYP) 3A4 to its major pharmacologically active metabolite, N-desethyl sunitinib, which is further metabolized to inactive compounds by the same enzyme.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the available evidence, the 2/1 schedule is relatively more effective and safer than the 4/2 schedule, and is feasible way to maintain drug level. 29,30 Comparison of intermittent versus continuous dosing regimens revealed that CDD does not have any advantage over 4/2 schedule in terms of the incidence or severity of AEs or patient-reported outcomes. 18…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis, the 2/1 (2 weeks on, 1 week off) schedule is more suitable than 4/2 (4 weeks on, 2 weeks off) for sunitinib in mRCC, due to superior progression-free survival, better disease control rate, and fewer AEs including fatigue [75,76].…”
Section: Improving Fatigue By Modifying the Dosing Schedule Of Vegfr-tki Therapymentioning
confidence: 99%